VRodel - A virtual sledding simulator - Jonas Kreiner; David Mikulic; Maximilian Gallinat; Stefan Kranhodlt; Gerald Kammerlander; Bernhard Hollaus (Bern Open Publishing, 2024)
Introduction & Purpose Sledding is a low-cost and accessible recreational activity popular in alpine regions. However, the risk of injury is high, especially for beginners or tourists, according to the Österreichisches Kuratorium für Alpine Sicherheit (2021). Therefore, promoting sledding safety is important to minimize the number of accidents and fatalities in the sport. Sterr (2019) says, the major reason behind an accident is often the lack of skill in steering the sled. Hence, it would be ideal to acquire the skill to steer before going on a track. In many fields skill training is done in virtual reality. Realism in skill training is a major aspect in the virtual worlds according to Newman et al. (2022). Therefore, the goal of VRodel was to create a virtual environment for training that is as close as reasonably possible to reality. Methods In the first step, an environment had to be chosen that would be safe yet effective for training the skill of steering the sled. Next, the sledding track of Kühtai was transferred to a virtual model by means of drone based photogrammetry. The three-dimensional model was then cleaned, polished, and set into the virtual valley that surrounds the track. In a third step, a game was developed in the virtual world to create a virtual training experience. Input from professional sledders and comparisons to time splits of the real track were used to adapt the physics. The user steers the sled by moving their hands in space to reflect the pulling of the reins and leaning into curves. To increase immersion, the safety training uses gamification aspects. As a fourth step, the game was tested by four experts from Rodel Austria and 49 beta-testers, which gave feedback about the realism. Results The project resulted in a virtual reality safety training for the sport of sledding, that excels the current sledding simulation games in terms of appearance and realism. This was underlined by the feedback from the experts of the Austrian Luge Federation and the beta-testers that gave the simulation an average score of 4.98 out on a scale from 1 to 7. In Figure 1, a glimpse of the virtual world is visible. Discussion Le Noury et al. (2022) mention the potential of extended reality for training a skill in sports in their review. They also outlined that this field showed low efficacy on improving motor skills in the past and more research is needed. This project is addressing the needs of society for safer luging and at the same time uses an approach that needs more research according to Le Noury et al. (2022). Therefore, not only the project's goals have been met, but also a contribution to the scientific progress in this field was made. Conclusion The immersive nature of the VRodel training program successfully engaged users, particularly children, through its gamified elements. Furthermore, this initiative not only enables sledding on a virtual track but also enables a study on the efficacy of virtual skill training in sledding. References: Le Noury, P., Polman, R., Malone, M., & Gorman, A. (2022). A narrative review of the current state of extended reality technology and how it can be utilised in sport. Sports Medicine, 52, 1473-1489. https://doi.org/10.1007/s40279-022-01669-0 Newman, M., Gatersleben, B., Wyles, K., & Ratcliffe, E. (2022). The use of virtual reality in environment experiences and the importance of realism. Journal of Environmental Psychology, 79, Article 101733. https://doi.org/10.1016/j.jenvp.2021.101733 Österreichisches Kuratorium für Alpine Sicherheit (2021). Der Zwischenbericht Winter 2021/22 liegt vor: 111 Alpintote in Österreichs Bergen (Mittel 10 Jahre: 113). Insgesamt verunfallten 6.716 Personen in Österreich. Die alpinen Unfallzahlen nehmen im Vergleich zum Vorwinter (2.476 Verunfallte) und dem langjährigen Mittel wieder Fahrt auf (Mittel 10 Jahre: 7.242) [The Winter 2021/22 interim Report is available: 111 Alpine fatalities in Austria's mountains (average 10 years: 113). A total of 6,716 people had an accident in Austria. Compared to the previous winter (2,476 accidents) and the long-term average (10-year average: 7,242), the number of alpine accidents is picking up again.]. https://alpinesicherheit.at/wp-content/uploads/2022/05/PA-2022-Winter-2021_22_12042022.pdf Sterr, R. (2019). Rodeln in Zahlen [Sledging in numbers]. ÖKAS, Österreichisches Kuratorium für Alpine Sicherheit. https://www.alpinmesse.info/de/Rodeln-in-Zahlen/